การสร้างหลักสูตรฝึกอบรมพยาบาลจบใหม่ที่เข้าสู่วิชาชีพ - เกศวหงษ์, รุ่งอรุณ (Ph.D. in Social Sciences Journal, 2016)
งานวิจัยนี้มีวัตถุประสงค์ เพื่อศึกษาสภาพปัญหาการปฎิบัติงานของพยาบาลจบใหม่และเพื่อสร้าง หลักสูตรและประเมินผลการทดลองใช้หลักสูตรฝึกอบรมพยาบาลจบใหม่ที่เข้าสู่วิชาชีพที่สร้างขึ้นโดยมี ผลการวิจัยสภาพปัญหาการปฎิบัติงานของพยาบาลจบใหม่คือ (1) ด้านความรู้ทางคลินิคได้แก่ การเขียน บันทึกทางการพยาบาลที่เชื่อมโยงกับการปฎิบัติการพยาบาล (2) ด้านทักษะการปฎิบัติการพยาบาลได้แก่ ขั้นตอนการให้สารละลายทางหลอดเลือดดำ (3) ด้านการปรับตัว ได้แก่ ความเครียดกับอารมณ์แปรปรวน ของผู้ร่วมงานและ (4) ด้านภาวะผู้นำและการสื่อสารได้แก่ ขาดความมั่นใจตนเองในการปฎิบัติงาน โครง ร่างหลักสูตรฝึกอบรมพยาบาลพี่เลี้ยงและ หลักสูตรฝึกอบรมพยาบาลจบใหม่ที่เข้าสู่วิชาชีพมีความเหมาะ สมในระดับมากถึงมากที่สุดและมีความสอดคล้องกันทุกองค์ประกอบและผลการนำหลักสูตรไปทดลองใช้ พบว่า พยาบาลพี่เลี้ยงมีความรู้หลังอบรมสูงกว่าก่อนอบรม อย่างมีนัยสำคัญที่ระดับ .05 และหลักสูตรฝึก อบรมพยาบาลจบใหม่ที่เข้าสู่วิชาชีพพบว่า พยาบาลจบใหม่มีความรู้ทางคลินิคหลังอบรมสูงกว่าก่อนอบรม และหลังอบรมไปแล้ว 3 เดือนยังคงสูงกว่าหลังอบรม ยกเว้น การดูแลผู้ป่วยวิกฤติระบบทางเดินอาหาร และต่อมไร้ท่อกับการดูแลผู้ป่วยวิกฤติระยะช็อคที่ไม่แตกต่างกัน ด้านทักษะการปฎิบัติการพยาบาลหลัง อบรมสูงกว่าก่อนอบรมและหลังอบรมหลังไปแล้ว 3 เดือนสูงกว่าหลังอบรมอย่างมีนัยสำคัญที่ระดับ .05 ด้านการปรับตัว ความเครียดและความวิตกกังวลหลังอบรมและก่อนอบรม และหลังอบรมไปแล้ว 3 เดือน กับหลังอบรมไม่แตกต่างกันและด้านภาวะผู้นำและการสื่อสาร หลังอบรมกับก่อนอบรม และหลังอบรมไป แล้ว 3 เดือนกับหลังอบรมไม่แตกต่างกัน ผลการวิจัยแสดงให้เห็นว่าหลักสูตรมีความคงทน สามารถนำไป แก้ปัญหาการปฎิบัติงานของพยาบาลจบใหม่ THE DEVELOPMENT OF NURSE RESIDENCY PROGRAM In this study, The objectives of the research were to study the work problems of newly graduated nurses and to design the courses of training program as well as the experimental evaluation of the courses after being trained. The research results of newly graduated nurse’s work problems in theirs work place were (1) clinical knowledge competency for nurse’s notes that related to nursing intervention (2) nursing intervention for the procedure of intravenous administration (3) adjustment for anxiety and colleagues’ moodiness (4) leadership and communication for the lack of self confidence to perform the task. The training program of mentoring and NRPs were found to be appropriate at a high level and the highest level and congruence with all factors. The results after the training program of mentoring as compared before and after participating in the program was found that the statistically significant level of .05 and the training program of NRPs was found that the clinical knowledge competency was significantly higher than before training and three months after training was higher as well except for critical care nursing of Gastro-intestinal and Endocrine patients as well as the patients with shock that were not different .The competency of nursing intervention (practice) was found higher after training and after three months of training were found that higher than after training at the statistically significant level of .05. The adjustment of anxiety before, after and after three months of training was not different. The leadership and communication, before, after and after three months of training were not different as well. Therefore, these courses of training are stable and able to be solved the work problems of newly graduated nurses.